Bibliometric Analysis of Teaching Factory Trends in Developing Entrepreneurial Spirit in Vocational Education - Raihan Ramadhan; Khilda Rahmi Zaki; Ganefri Ganefri; Asmar Yulastri; Yudha Aditya Fiandra (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to map scientific publication trends related to Teaching Factory and the development of entrepreneurial spirit in the context of vocational education. Bibliometric analysis was conducted using data taken from the Scopus database for the period 2019 to 2024. The data were analyzed using VOSviewer software to identify publication trends, frequently used keywords, collaborations between authors, and the dynamics of research topics over time. The visualization results show that the topics of Teaching Factory and entrepreneurship education are central themes that are closely connected with keywords such as education, development, vocational colleges, and innovation. In addition, research trends show a shift in focus from a conceptual approach to a more applied and innovative approach in vocational education. These findings provide a comprehensive overview of the direction of research development in the field of vocational education and offer a strong foundation for further research, particularly those focused on the integration of industry-based learning and strengthening entrepreneurial competencies.